Ethical implications in hospital care among people with intellectual disabilities: a narrative review - Reto, Narcisa (2022)
People with intellectual disabilities (PID) are prone to complications during some illnesses due to their comorbidities, thus requiring differentiated hospital care. However, they do not usually receive an appropriate treatment and their rights are often violated, especially in the ethical field. The principles of justice, non-maleficence, beneficence and autonomy could be violated in hospital settings not only by health personnel, who sometimes provide dehumanized treatment and with little involvement of the caregiver, but also by hospital care systems, which do not consider PID’s limitations, inequalities and priority needs. To identify this reality, the present narrative review was conducted, finding 484 articles in databases such as PubMed, Scopus and LILACS, out of which 53 were included. The scarcity of information directly related to ethics in hospital care stands out; however, related topics such as reproductive health, transplantation, management of chronic diseases and health promotion were analyzed, mainly highlighting the lack of autonomy and justice. After the review, it was concluded that it is important to disseminate ethical principles to all healthcare personnel, from the beginning of their education, as well as to sensitize healthcare decision-makers regarding the treatment of PID, especially in hospital settings, where a differentiated and fair care system that favors integration, access and communication is required.